Internal v. external rent-seeking with in-group inequality and public good provision - Dripto Bakshi; Indraneel Dasgupta (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2021)
We examine how inequality in the endowment of secure wealth, mediated through voluntary public communities, each internally differentiated into rich, intermediate and poor segments, contest one another for the division of some rent. Any rent accruing to a community is distributed internally according to another, simultaneous, contest. Individuals first decide how much of their endowments to allocate to the two contests. They subsequently decide how to allocate their remaining wealth and rental income between private consumption and a community-specific public good. We find that greater endowment inequality among the non-rich, both within and across communities, aggravates inter-group rent-seeking. Within-group rent-seeking may rise as well. In contrast, higher such inequality between the rich and others within a community depresses between-group conflict. Within group conflict may fall as well. The 'paradox of power' is violated for both kinds of conflict - better endowed individuals are more successful in the internal conflict, while better-endowed groups are more successful in the external conflict.
Keywords: D72; D74; 330; Internal v. external rent-seeking; Ethnic conflict; Intra-group inequality; Inter-groupinequality; Public good provision